Um modelo exploratório para o processo de compra de MRO baseadas na internet Michelin Brasil - Peres, Walter José (2001)
The present dissertation is intended to create a purchasing model of MRO (maintenance, repair and operations) based on the Internet, for Michelin in Brazil. Current1y, Michelin' s enterprise is part of a virtual community, under the vertical portal form, created by the greatest industry enterprises in tire and rubber field (Michel in, Goodyear, Pirelli, Continental, Cooper, Sumitomo, and others), with the intention to develop a global market place to realize purchases and supplies. Rubbernetwork.com (RNC) was founded as an independent enterprise, gathering the complexities of the tire and rubber industry, which represents an amount over fifty billion dollars a year spent on raw materiais, equipment, machines, goods and services. This purchasing center will allow the members to increase the efficiency of their operations and realize great savings on business costs. Each business transaction will be protected by the appropriate systems from the implement of the information technology, with the objective to assure confidentiality for alI commercial activities on each enterprise individually. The participating members are convinced that this initiative will alIow substantial savings and it will improve their chain value. The virtual community will be opened to alI manufacturers and providers related to the tire and rubber industry, and it will also welcome interaction opportunities with other virtual communities, especially those associated to the automobile industry. 5 It is under the context of the implementation of the Rubbernetwork.com (RNC) that the dissertation will be developed, scheming strategies and concerning purchasing processes related to MRO (maintenance, repair and operations). The development of vertical portal on Internet does not impede horizontal complementary portaIs, not excluding, also to be increased as business alternative. We shall give specific attention to daily purchasing that involves a great number of different suppliers, various internaI areas in the enterprise that spend time on unnecessary bureaucratic work, without strategic finalities. We must emphasize that this category of purchasing, named MRO, despite its low value per product or acquired services, generates a huge volume oftransactions and a high operational impacto Toward the fact that is an innovated expenence In the sector with proper characteristics - tire and rubber market - , and because it is creating an expectation of cooperation between concurrent enterprises, that are searching for rationalization of purchasing process and division of operational costs, the adopted methodology, as its finality it will be exploratory and applied2 . As its investigation's means, the realized research will be: on field, study of case and bibliographic. The research' s umverse will be restricted to Michelin enterprise, where the purchasing process of MRO based on Internet will be contemplated, by the collection of facts in the USA and France, with the intent to propose a model to Michelin in Brazil.